THE MEANING OF PHYSICAL BOUNDARY OF REAL ESTATE FOR PEOPLES LIVING IN SURROUNDING KAMPONGS IN SOUTH TANGERANG - Budi Utami, Tin
The physical boundaries of real estate in between surrounding kampongs are constructed by the developers in various forms. It can be designed to be well integrated to the surrounding society so that it leads to a harmony. On the other hand, the physical boundaries of real estate could lead to problems if it is designed without looking into the condition of the surrounding society. Those facts reveal that various types of physical boundary of real estate can be interpreted differently by the surrounding society. This dissertation research is intended to explain the response of the people in the surrounding of real estate towards the existence of physical boundaries which are built by the developer in South Tangerang, with the study case of Bintaro Jaya. The purposes of the study are (1) to identify the range of typologies and characteristics of the physical boundaries of real estate which is directly adjacent to the surrounding kampongs, (2 ) to describe the perceptions and meanings given by the people around the physical boundaries of the real estate to each typology and character of the existing physical boundaries, as well as the factors that influence it, and (3) to analyze the pattern of the relationship between perception and public response to empirical condition of the existing real estate physical boundary. Literature review is conducted by collecting theories and research findings related to the phenomenon of real estate and its surrounding kampongs, especially in relation to: the parameters of physical boundaries of real estate? the function of physical boundaries of real estate? the indicators to evaluate the perception and the meaning of physical boundaries of real estate for society. In order to assess the physical boundary conditions of the real estate and to measure the response given by the society, five indicators of research are used which consist of: access to essential resources, residence environment, relationships with institutions, social cohesion, and participation. The initial research has produced 9 typologies of physical boundaries of real estate which are distinguished based on five parameters, namely: access availability, character, observation distance, contour differences, and height. The study was conducted using comparison method between the physical boundary empirical conditions of the real estate with the perception and the meaning given by the community. The data collection on the physical boundary conditions of the real estate is done through surveys, observations, and interviews with sources who understand the real estate development process. Data collections on the perception and meaning are implemented through structured interviews conducted with the people living in the surrounding real estate. Empirical data processing and perceptions were performed using distribution and Anova analysis to identify the factors that significantly affect the perception and the meaning given by the society to the physical boundaries of the real estate. The results show that: 1) Physical boundary conditions of real estate do not affect the creation of social cohesions between the occupants of the real estate and community in the surrounding villages, but those conditions are very influential with regard to the availability of access towards essential resources and residence environment for the community in the surrounding kampongs. Social cohesions are relatively good for both good and bad condition of real estate physical boundary, while the access availability towards essential resources and residence environment are significantly related to the condition of each typology of the physical boundaries of real estate? 2) The relationship to institution and participation are relatively bad both good and bad condition of typology of real estate physical boundary. Government has not played an ideal role to control the construction of physical boundaries of real estate, while the participation of the society in managing the boundaries is still so low that it is prone to conflict? 3) The society perception towards the design of real estate physical boundary is influenced by their social and economic background and their motive to access the real estate area. A better perception will be given if the dependency of their activities inside the real estate area is higher. Physical boundary of real estate can be a potential communal space to be developed for two different settlements, otherwise if ignored will be the source of problems for stakeholder. In order to create physical boundary of real estate which are good and responsive towards the necessity of the surrounding kampong residents, it requires the commitment and participation of all stakeholders, including the government, developers, social agencies, real estate occupants and kampong residents around the real estate.